Plasma system with rotational gliding arc between solid electrodes - Solomenko, O.V.; Nedybaliuk, O.A.; Chernyak, V.Ya.; Martysh, E.V.; Fedirchyk, I.I.; Prysiazhnevych, I.V. (Вопросы атомной науки и техники, 2013)
Rotational gliding arc with solid electrodes has been studied at different flow of working gas (air). Plasma torch studies by emission spectroscopy method. Measurements have been made at various levels from the electrode surface along the entire flare height. Electronic temperature levels of plasma component population have been determined. Current-voltage characteristics under different operating conditions were investigated. Досліджувалась обертова ковзна дуга з твердими електродами за різних потоків робочого газу (повітря). Проводилися дослідження плазмового факелa методом емісійної спектроскопії. Виміри проводились на різних рівнях від поверхні електроду вздовж усієї висоти факелa. Визначені температури заселення збуджених електронних рівнів компонент плазми. Досліджені вольт-амперні характеристики при різних режимах роботи. Исследовалась вращательная скользящая дуга с твердыми электродами при различных потоках рабочего газа (воздуха). Проводились исследования плазменного факела методом эмиссионной спектроскопии. Измерения проводились на разных уровнях от поверхности электрода вдоль всей высоты факела. Определены температуры заселения возбужденных электронных уровней компонент плазмы. Исследованы вольт- амперные характеристики при различных режимах работы.